Code switching among ABEL students in selected literature class - Haban, John Mark P. (PSU Urdaneta Campus Research Journal, 2015)
This study dealt with the following objectives: (1) to determine the profile of the respondents in terms of type of high school graduated from, grade in English subjects, reading material preferences, and attitudes towards code switching; (2) to determine the extent of the use and seriousness of code switching in class discussion; (3) to determine the main reasons of the respondents in using code switching along domain, interlocutor, topic, and function; and (4) to asses the relationship of the respondents' profile with the frequency of code switching. The respondents included the entire population of the bona fide sophomore ABEL students of Pangasinan State University, Urdaneta Campus, who were enrolled in the course "Literary History of the Philippines" during the Second Semester, Academic Year 2015-2016. The descriptive-correlational research design was employed in this study. The researchers used voice recorder and questionnaire to gather all the needed data to arrive at a definite conclusion. It was then supplemented by direct personal inquiry of the researchers to the respondents so as to ensure the accuracy and integrity of the recorded data. Frequency, percentage, mean, ranking, and contingency coefficient were the statistical tools utilized to analyze and interpret the data gathered. The findings showed that most of the sophomore ABEL students graduated from public high schools; their grades in the English subjects are fair; majority of them preferred English over Filipino reading materials; and they have shown highly favorable attitudes towards code switching. Moreover, the data from the three recordings revealed a very high frequency of code switching. In addition, the statement "I use code switching when I cannot think of the term in English and a Filipino term is available" is the main reason of the respondents for switching codes. Lastly, the results showed no dependence between the profile of the respondents and the frequency of code switching. The following are the highlight6s of the study: (1) the sophomore ABEL students are typically characterized as public school high school graduates, who have fair academic performance in their English subjects, who preferred English over Filipino reading materials, and who have shown highly favorable attitude towards code switching; (2) there is a very high frequency of using code switching in the class discussion which indicated a very serious impact on the respondents' mastery of the English language; (3) there are different reasons why the respondents use code switching in class discussion, including domain, interlocutor, topic, and function; and (4) the profile of the respondents has no to little influence with the frequency of code switching. It is then recommended based on the conclusion that the students make all the necessary efforts to avoid using code switching in class discussion so as to improve their communicative competence in the English Language. In addition, the instructors should discourage the habitual use of code switching as it affects the students' development in becoming linguistically and communicatively competent. Moreover, the University Administrators, together with the College Deans, Department Chairs, and Instructors of the English Language Department, are strongly encouraged to take remedial measures to lessen the use of code switching in the classroom. Lastly, a similar study is encouraged to be conducted, provided more variables and more respondents be included so as to further establish the results of this study. It is also recommended and encouraged that a similar study be conducted in a language class and compare the frequency between language and literature class.